2011
DOI: 10.1007/s10103-011-0952-8
|View full text |Cite
|
Sign up to set email alerts
|

The pulsed dye laser for the treatment of basal cell carcinoma

Abstract: Basal cell carcinomas (BCC) have a specialized microvasculature system that can be targeted by the 585-nm pulsed dye laser (PDL) utilizing the theory of selective photothermolysis. Seven volunteers with nine well-defined, biopsy-proven BCCs, were treated with the PDL (585-nm wavelength, a single 450-μs pulse, 7-mm spot size, and 9.0 J/cm(2) energy). The lesions, along with a 4-mm border of normal skin were treated. Pain assessment was carried out immediately after the laser treatment. A deep shave biopsy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 13 publications
1
22
0
2
Order By: Relevance
“…[3][4][5] Laser treatment is suitable for certain types of patients such as those who may have multiple BCCs due to underlying hereditary disorders, excessive sun exposure or longterm immunosuppression, or those who may not tolerate surgical procedures, or those who may have low tolerance for the inflammatory side effects of topical therapies. [5][6][7][8] Laser ablation, e.g., is effective for treating superficial and nodular BCCs. [9][10][11] The treatment is relatively quick and convenient to perform in a single patient visit, and is minimally invasive, with finely controlled micrometer-level removal of tissue, reduced bleeding, scarring and infection, quicker recovery, and better cosmetic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Laser treatment is suitable for certain types of patients such as those who may have multiple BCCs due to underlying hereditary disorders, excessive sun exposure or longterm immunosuppression, or those who may not tolerate surgical procedures, or those who may have low tolerance for the inflammatory side effects of topical therapies. [5][6][7][8] Laser ablation, e.g., is effective for treating superficial and nodular BCCs. [9][10][11] The treatment is relatively quick and convenient to perform in a single patient visit, and is minimally invasive, with finely controlled micrometer-level removal of tissue, reduced bleeding, scarring and infection, quicker recovery, and better cosmetic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported CR rates ≥ 75%, which is acceptable [16,18], whereas in the remaining studies the CR rates were lower, ranging between 62% and 14% [13,14,17,19]. The number of PDL sessions is decisive for the treatment outcome: Amongst the 104 BCC treated with a 595-nm device, only 6/13 (CR: 46%) were cleared after a one-session scheme as opposed to 69/91 (CR: 76%) of the tumors treated with multiple 3-5 sessions (p = 0.0432; Fisher's exact test).…”
Section: Review Of the Use Of Monomodal Pdl For Bccmentioning
confidence: 89%
“…However, efficacy assessment of the PDL-based approach is obscured by the diversity of treatment parameters employed in the existing studies, as well as the methods applied to measure treatment outcomes (clinical follow-up or histopathological evaluation of completely excised tumors taken at different time intervals after PDL treatment). Moreover, in some studies only one PDL treatment session was allowed [13,14,19], whereas in the others, 3-5 sessions were planned on different days [15][16][17][18]20]. Overall, 81/120 (67.5%) treated tumors have been assessed as complete responders (CR).…”
Section: Review Of the Use Of Monomodal Pdl For Bccmentioning
confidence: 99%
See 1 more Smart Citation
“…Publicaciones recientes muestran la eficacia de los láseres vasculares en el tratamiento del carcinoma basocelular [46][47][48][49][50] . Sin embargo, se postula que esta técnica podría tener el riesgo de que las posibles recidivas muestren un crecimiento multifocal, de modo parecido a lo que ocurre con las recidivas después de la crioterapia.…”
Section: Cáncer De Piel No Melanomaunclassified